2013
DOI: 10.1016/j.ijgo.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics, and outcomes of HIV‐positive women diagnosed with invasive cancer of the cervix in Kenya

Abstract: Objective: To determine the prevalence of invasive cervical cancer (ICC) and assess access to, and outcomes of, treatment for ICC among HIV-infected women in Kisumu, Kenya. Methods: We performed a retrospective chart review to identify women diagnosed with ICC between October 2007 and June 2012, and to examine the impact of a change in the referral protocol. Prior to June 2009, all women with ICC were referred to a regional hospital. After this date, women with stage IA1 disease were offered treatment with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Studies from Kenya found that the majority of HIV-positive women, who underwent cervical cancer screening, had stage 1 disease at the time of diagnosis of invasive cervical cancer and this was attributed to the availability of screening. 27 This aspect is consistent with our study, which found the biggest factor associated with cervical cancer disease stage is whether the women were screened or not. However, there was not much difference in cervical cancer disease stage based on the HIV status.…”
Section: Discussionsupporting
confidence: 92%
“…Studies from Kenya found that the majority of HIV-positive women, who underwent cervical cancer screening, had stage 1 disease at the time of diagnosis of invasive cervical cancer and this was attributed to the availability of screening. 27 This aspect is consistent with our study, which found the biggest factor associated with cervical cancer disease stage is whether the women were screened or not. However, there was not much difference in cervical cancer disease stage based on the HIV status.…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, the present study was the first to estimate the marginal costs of integrating cervical cancer screening into HIV clinics from a societal perspective (including opportunity costs of patients' time) in a Kenyan or Sub‐Saharan African setting. This addresses an existing knowledge gap on the costs of integrating cervical cancer screening into existing public health programs and could assist health systems in leveraging existing resources to increase screening coverage . Additionally, the various scenarios analyzed highlight variations in costs that occur under different model assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in the urban center of Nairobi have found the prevalence of HPV infections and high‐grade pre‐cancerous lesions to be 49%–69% and 24%–27% for among women with HIV, respectively; these figures are in comparison with 17% and 8% among women without HIV, respectively . Research performed in Western Kenya has suggested that women living with HIV have a two‐ to four‐fold higher risk of developing cervical cancer compared with women without HIV …”
Section: Introductionmentioning
confidence: 99%
“…The mean age at diagnosis was 34 years (range 22-50 years) and 93 % had microscopic disease (stage IA1) (Mungo et al 2013 ). Another retrospective study from South Africa found that HIV-positive women were diagnosed with ICC at a younger age and more advanced stage than HIVnegative women.…”
Section: Invasive Cervical Cancermentioning
confidence: 99%